(untitled) (Global Journal of Human-Social Science, 2022)
This paper examines mimicry as an opportunistic pattern of behavior where women or the oppressed copy or imitate the lifestyle pattern language values dress codes and food of people in power with the hope or desire to have access to that same power in the future in Ted Elemeforo s Fountain of Betrayal Although the concept of mimicry has received significant attention Fountain of Betrayal has not been examined along this axis Furthermore most of these earlier studies conceived mimicry only as an attempt by the colonized black to mimic the colonizer white